The classical tradition in medieval Catalan, 1300-1500 : translation, imitation, and literacy - Cabre, Lluis, 1959- (Colección Támesis. Monografías ;, 2018)
The first comprehensive study of the reception of the classical tradition in medieval Catalan letters. This book offers the first comprehensive study of the reception of the classical tradition in medieval Catalan letters, a multilingual process involving not only Latin and Catalan, but also neighbouring vernaculars like Aragonese,Castilian, French, and Italian. The authors survey the development of classical literacy from the twelfth-century Aragonese royal courts until the arrival of the printing press and the dissemination of Italian Humanism. Aimed atstudents and scholars of medieval and early modern Iberia - and anyone interested in medieval Romance literatures and the classical tradition - this volume also provides a concise introduction to the medieval Crown of Aragon, a catalogue of translations into Catalan of texts from classical antiquity through the Italian Renaissance, and a critical study of the influence of the classics in five major works: Bernat Metge's Lo somni, Joanot Martorell'sTirant lo Blanc, the anonymous Curial e Güelfa, Ausiàs March's poetry, and Joan Roís de Corella's prose. Lluís Cabré is associate professor of medieval Catalan literature at the Universitat Autònoma dercelona; Alejandro Coroleu is ICREA research professor of Renaissance Humanism at the Universitat Autònoma de Barcelona; Montserrat Ferrer is a research associate at the Universitat Autònoma de Barcelona; Albert Lloret is associate professor of Spanish and Catalan at the University of Massachusetts Amherst; Josep Pujol is associate professor of medieval Catalan literature at the Universitat Autònoma de Barcelona.